CONTENTS OF ESSENTIAL AMINO ACIDS OF SOME MEXICAN SEEDS - TORRE CALVO, JOSE DE LA; MASSIEU H , GUILLERMO; GUZMAN, G JESUS; CRAVIOTO, RENE O (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
Seeds of various kinds were analyzed microbiologically As compared with the essential amino acid content of whole egg protein,high contents of lysine were found in chick peas, lentils, dry peas, broad beans, "parota" (Enterolobium cyclocarpum), and "pata
CIENC MEX
Keywords: CONTENTS, ESSENTIAL, AMINO- ACIDS, MEXICAN, SEEDS; MULTIDISCIPLINARIA; CIENCIAS DE LA NUTRICION; NUTRIENTES